Assessing transformative change of infrastructures in urban area redevelopments - Jain, Mansi; Rohracher , Harald (Elsevier Ltd, 2022)
Urban redevelopments create opportunities for experimenting with innovative infrastructural solutions towards transformative urban change. Novel solutions such as decentralised infrastructure systems can become essential strategies for helping cities meet multiple sustainability outcomes. However, achieving infrastructural change is a tremendous challenge given the obduracy of these large and complex systems. Assessing and monitoring ongoing infrastructure shift, transformative urban systems needs to provide a better understating of how to account for systemic change. This paper addresses the challenge of assessing and monitoring urban transformative change in a forward-looking and systematic way. A conceptual assessment framework is developed, which identifies key critical dimensions necessary to assess the transformative change potential in the context of urban redevelopment areas. These include the shaping of new expectations/visions, the establishment of new social networks, the creation of learning processes, institutional alignment, and the establishment of new modes of governance. The conceptual framework is applied in a case study of selected urban redevelopment sites in New Delhi, India. The framework was found useful which gaining a differentiated understanding of the transformation process and identifying the strengths and weaknesses within the urban redevelopment niche that can potentially support or obstruct the transition process.
Keywords: Evaluation; Learning; Sustainable infrastructures; Urban redevelopment; Urban transformative change; Development; Sociology and Political Science; Urban Studies; Tourism, Leisure and Hospitality Management; SDG 11 - Sustainable Cities and Communities